2017
DOI: 10.1016/j.jcs.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The agronomic performance and nutritional content of oat and barley varieties grown in a northern maritime environment depends on variety and growing conditions

Abstract: This is the author accepted manuscript. The final version is available from Elsevier via http://dx.doi.org/10.1016/j.jcs.2017.01.005Warmer temperatures and increasing interest in high provenance food and drink products are creating new opportunities for cereal growing in northern Europe. Nevertheless, cultivation of oats and barley in these areas for malting and milling remains a challenge, primarily because of the weather, and there are few reports of their nutritional content from this region. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
0
26
4
1
Order By: Relevance
“…In some cases, the differences are significant. For example, samples from the United Kingdom (UK) contain significantly lower concentrations of Cd, Pb, Cr and Ni, and higher concentrations of Cu (Chapell et al, 2017). Samples from East regions of Turkey have higher concentrations of Cu and K (Dembiras, 2005), in samples from Poland the content of Na is significantly lower (Rybicka, Gliszczyńska-Świgło, 2017) than in our samples.…”
Section: Concentration Of Macro and Trace Elements In Oat Grain Depenmentioning
confidence: 55%
“…In some cases, the differences are significant. For example, samples from the United Kingdom (UK) contain significantly lower concentrations of Cd, Pb, Cr and Ni, and higher concentrations of Cu (Chapell et al, 2017). Samples from East regions of Turkey have higher concentrations of Cu and K (Dembiras, 2005), in samples from Poland the content of Na is significantly lower (Rybicka, Gliszczyńska-Świgło, 2017) than in our samples.…”
Section: Concentration Of Macro and Trace Elements In Oat Grain Depenmentioning
confidence: 55%
“…(2011) and Chappell et al. (2017) have shown that 1,000‐grain weight to be both positively and negatively associated with β‐glucan content.…”
Section: Resultsmentioning
confidence: 97%
“…Chappell et al. (2017) indicated that seasonal effect may be more important in determining the molecular weight of β‐glucan rather than the total content. However, Griffey et al.…”
Section: Resultsmentioning
confidence: 99%
“…Barley grain is rich in proteins, starch, vitamins, and other bioactive constituents (Chappell et al, ). The chemical composition of barley with different varieties was summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Barley grain is rich in proteins, starch, vitamins, and other bioactive constituents (Chappell et al, 2017). The chemical composition of barley with different varieties was summarized in Table 1 sharp decrease was observed during the first 12 hr and followed by a slower rate from 24 to 48 hr for all LFBEs.…”
Section: Chemical Composition Analysismentioning
confidence: 99%